PREVALENCE OF LOW BACK PAIN AMONG THE UNDERGRADUATE STUDENTS OF ISRA UNIVERSITY KARACHI CAMPUS (International Journal of Physiotherapy, 2016)
Background: LBP is a condition with a high prevalence and recurrence rate. This condition has the potential to create a major impact on the individual over extended periods of time. Numerous reasons and factors for lower back pain have been suggested; including age, gender, body mass index (BMI) and physical activity of the patient. There are different treatments and techniques being implemented, however their effects are minimal. Students at University level are at high risk of LBA due to prolonged sitting and standing hours.Methods: Research was conducted on 190 students of ISRA University, Karachi Campus. The duration of the study was 6 months, the participants were randomly selected, who were studying in ISRA University, Karachi Campus and self-administered questionnaires with consent forms were distributed to all the participants. Participants were asked to complete the questionnaire and return it to the concerned person after one week.Results: 71.6% had history of low back pain whereas 28.4% did not have history of low back pain. 84.7% students used computer whereas 15.3% did not use computer. 65.3% left the class room due to low back pain whereas 34.7% did not leave the class room. 61.6% students had prevented normal work from 1-7days due to low back pain during last 12 months, 26.8% prevented normal work from 0 days whereas 11.6% students had prevented normal work from 8-30days due to low back pain during last 12 months.Conclusion: The overall aim of this study was to analyze the prevalence of low back pain among the undergraduate students of ISRA University, Karachi Campus. The study provided a detailed awareness about the level of prevalence of lower back pain among the undergraduate students. The results of this study showed that most of the students were experiencing lower back pain, and it was also found that it is directly related to their work.